Wideband CMOS image reject downconverter - Kaufik Linggajaya. (2008)
This work investigates the implementation of image reject downconverters that give sufficient image rejection across operation bandwidth. The implementation of four image reject architectures, the Hartley image reject downconverter, the Weaver image reject downconverter, the image reject downconverter with passive polyphase filters.